2005
DOI: 10.1111/j.1399-0039.2005.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I and II polymorphisms in Azores show different settlements in Oriental and Central islands

Abstract: Human leucocyte antigen-A, -B, -Cw, -DRB1, -DQA1 and -DQB1 polymorphisms were examined in the Azorean population. The data were obtained at high-resolution level, using polymerase chain reaction (PCR) with sequence-specific primer, PCR-sequence-specific oligonucleotides and sequence-based typing. The most frequent allele in each locus was: A*0201 (24.5%), B*510101 (9.8%), Cw*0401 (14.8%), DRB1*070101 (18.3%), DQA1*0201 (17.4%) and DQB1*0301 (19.4%). The predominant extended haplotype was A*0202-B*1503-Cw*0202-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…This haplotype is found at low frequency only in European and North American populations [14] but has a 1.3% frequency in the Azores [22]. The state of Rio Grande do Sul experienced a strong Azorean immigration during the 18th century.…”
Section: Resultsmentioning
confidence: 97%
“…This haplotype is found at low frequency only in European and North American populations [14] but has a 1.3% frequency in the Azores [22]. The state of Rio Grande do Sul experienced a strong Azorean immigration during the 18th century.…”
Section: Resultsmentioning
confidence: 97%
“…This may be a direct consequence of the Azorean settlement, with a major contribution of mainland Portuguese (~60%) and, to a lesser extent, Flemish, Spanish, French, Italians, Germans, Scottish, Jews, Moors and blacks from Guinea, Cabo Verde and São Tomé. Previous studies of HLA markers in mainland Portugal (3 loci , -A, -B and -DRB1, [18]) and in Azores (6 loci , -A, -Cw, -B, -DRB1, -DQA1 and -DQB1, [5]) demonstrate values of average diversity of 0.92 in both populations. The results obtained in the present study, based in 7 loci , showed a smaller value (0.84).…”
Section: Discussionmentioning
confidence: 98%
“…Principal Components Analysis (PCA) for 38 populations with HLA-B data available was performed using the IBM SPSS Statistics 19 software ( IBM Corporation, Armonk, NY, USA ) to analyse the distribution of HLA-B alleles in human groups of the proposed ancestries, Figure 1 . PCA included population data of Ireland [20], NW of England [61], Germany [62], Austria [63]; Spain, Italy, United Kingdom [64], France [65], Gypsy from Andalucía (Spain; data collected by López-Nevot et al ) [14], Azores Terceira Island [66], Forro from São Tomé Island [67], Beti from Cameroon [68], Bandiagara from Mali, Lusaka from Zambia, Luo and Nandi from Kenia [69], Mandeka from Senegal [70], Guinea Bissau [71], Aleut from Bering Island (Russia) [72], center of Japan [73], a cord blood bank of Tzu Chi Foundation (Taiwan) [74], Han from southern China [60], north India [75], Kensiu from Malasya [76], Kinh from Vietnam [77], Tarahumara from northern Mexico [17], Native Americans from Gila River (USA) [78], Yu’pik from Alaska (USA) [79], Mixtec, Zapotec, and Mixe from Oaxaca (Mexico) [16], Seri from Sonora (Mexico) [80], Navajo from New Mexico (USA) [81], Uro from Titikaka Lake (Peru) [82], and Toba from Rosario (Argentina; data collected by Cintia Marcos et al ) [14]. Also, two admixed populations from Mexico were included: a “Mexican Mestizo” sample [83] and a sample from Guadalajara City, western Mexico [23].…”
Section: Methodsmentioning
confidence: 99%